2020
DOI: 10.1007/s10919-020-00337-z
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Voice Intonation: A Communication Code at the Origins of Speech Processing and Word-Meaning Associations?

Abstract: The aim of the present work is to investigate the facilitating effect of vocal emotional intonation on the evolution of the following processes involved in language: (a) identifying and producing phonemes, (b) processing compositional rules underlying vocal utterances, and (c) associating vocal utterances with meanings. To this end, firstly, I examine research on the presence of these abilities in animals, and the biologically ancient nature of emotional vocalizations. Secondly, I review research attesting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 196 publications
(192 reference statements)
0
4
0
Order By: Relevance
“…The hypothesized common ancestor is often referred to as "musilanguage" (Brown, 2000), "musical protolanguage" (Fitch, 2005), or "prosodic protolanguage" (Fitch, 2006). A growing number of researchers further emphasizes the idea that affective/emotional and iconic vocalizations could have played a significant role in the joint evolution of speech and music (Rousseau, 1781;Darwin, 1871;Fonagy, 1981;Levman, 1992;Scherer, 1995;Thompson et al, 2012;Perlman and Cain, 2014;Brown, 2017;Filippi and Gingras, 2018;Reybrouck and Podlipniak, 2019;Filippi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesized common ancestor is often referred to as "musilanguage" (Brown, 2000), "musical protolanguage" (Fitch, 2005), or "prosodic protolanguage" (Fitch, 2006). A growing number of researchers further emphasizes the idea that affective/emotional and iconic vocalizations could have played a significant role in the joint evolution of speech and music (Rousseau, 1781;Darwin, 1871;Fonagy, 1981;Levman, 1992;Scherer, 1995;Thompson et al, 2012;Perlman and Cain, 2014;Brown, 2017;Filippi and Gingras, 2018;Reybrouck and Podlipniak, 2019;Filippi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Step 3: Manipulation of tone and emotions to increase panic Studies on vocal emotional intonations have consistently shown that emotional valence in speech allows interlocutors to infer communicative functions such as comforting, alerting, disapproving, or alarming (Dolan, 2002;Fernald, 1992;Filippi, 2020;Trainor et al, 2000). Fernald and colleagues (1989) found this to be consistent across human societies.…”
Section: Evidencementioning
confidence: 99%
“…Even in the proto-conversations that infants have with adults, affection is shared, based on the exchange of glances, smiles, and vocalisation [6]; just as voice modulation or prosody is fundamental when emotions are transmitted or received in preverbal humans [7]. The latter author points out that, as hypothesised by Darwin, the ability to express emotions through voice modulation was a key step in the evolution of spoken language.…”
Section: Introductionmentioning
confidence: 99%